PHYSICO-CHEMICAL MONITORING OF LAKE WATER DURING IDOL IMMERSION - Dwivedi, Bharti; Banerjee, Suchitra (International Journal of Research -GRANTHAALAYAH, 2018)
The present study concerns on physicochemical monitoring of the water quality nature and the extent of pollution in lake due to idol immersion. Pre-immersion and post immersion samples were collected from lake and analyzed for various water quality parameters such as pH, turbidity, total dissolve solid (TDS), total solid (TS) total suspended solid (TSS), conductivity phosphate, dissolved oxygen (DO), BOD, COD and oil & grease. The results were compared with standards prescribed by WHO and ISI. From the study, it has been found that the values of these parameters significantly increased during the immersion period and the declined in post immersion period. However the general trend observed was: immersion> Post immersion> pre immersion.The article focused on the main pollution which is caused by plaster of Paris idols and chemical paints by idol immersion during Ganesh festival.